Pediatric Clinical for Nursing Students in Rural Areas: The Camp Nursing Experience - Lori Hendrickx; Heidi Pelzel; Linda Burdette; Nancy Hartung (Online Journal of Rural Nursing and Health Care, 2020)
Problem: Clinical placement for nursing students in pediatrics can be challenging in rural settings. Hospitals in rural areas typically do not have the numbers of pediatric patients necessary to provide individual inpatient pediatric experiences for a group of nursing students nor can community settings accommodate a full group of students at once. Children’s hospitals or hospitals with pediatric inpatient units are often a significant distance from nursing programs located in rural areas and there is competition among nursing programs for placement in these facilities. A study by the Institute of Pediatric Nursing (IPN) in cooperation with the American Association of Colleges of Nursing (AACN) concluded that nursing schools had challenges finding pediatric clinical sites and that pediatric content was lacking in depth and breadth (McCarthy & Wyatt, 2014).